Analysis Produk Keuangan Syariah Sukuk - Trimulato, Trimulato (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2021)
The development of the financial industry continues increase people are increasingly interested in using Islamic financial products. The products offered are increasingly varied to meet the needs of the community. In addition to providing benefits, Islamic financial products can contribute widely to the development of the country, in this case, the Sukuk product. Legally, Sukuk or Islamic bonds, get the law first, when compared to Islamic banks. Sukuk has law number 19 of 2008 concerning State Sharia Securities (SBSN). The Sukuk instrument continues to grow and can provide benefits for investors and benefits for the country's development. The purpose of this study is to determine the development of state Sukuk products, and analysis of Islamic financial products. The method used is qualitative, with a literature study approach. The data sources used are secondary data, data that has been presented by certain institutions and then processed, and from other sources deemed relevant to the theme. The data collection technique used is literature study from several sources, both from books, journals, and others. The analytical technique used is descriptive qualitative, describes the development of Sukuk products in 2020 to 2021, and describes the analysis of the Sukuk ijarah products. The results of this study indicate that there are developments in state Sukuk in the 2019 to 2020 period, PBS Auction Sukuk, PBS Private Placement Sukuk, SNI, SPN-S, Rite Sukuk (SR), and Savings Sukuk (ST) grew by 40.80 percent. Auction PBS Sukuk grew by 39.59, PBS Private Placement Sukuk grew by 214.39%, SR grew by 72.93%, SNI Sukuk by 26.86 percent. Meanwhile, SNI Sukuk decreased by -30.01% and ST decreased by -35.76 percent. Analysis of Islamic sharia financial products, especially with the ijarah scheme. There is a sale and purchase transaction is considered engineered, then the resale of assets from the investor to the issuer such as a sale and purchase transaction is prohibited. Buying and selling of Sukuk assets which are then leased back and have a time limit and conditions on the object of sale and purchase, making the seller not have control over the asset. Then the sale and purchase can become a sale and purchase without the obligation to resell the product that has been purchased if the owner of the goods can return the money for the goods he sells.